Control psychophysical children's development under the correction movement disorder - B O Bukhovets (Kazimierz Wielki University, 2016)
Bukhovets B. O. Control psychophysical children's development under the correction movement disorder. Journal of Education, Health and Sport. 2016;6(2):200-210. eISSN 2391-8306. DOI http://dx.doi.org/10.5281/zenodo.46410 http://ojs.ukw.edu.pl/index.php/johs/article/view/3393 https://pbn.nauka.gov.pl/works/716436     The journal has had 7 points in Ministry of Science and Higher Education parametric evaluation. Part B item 755 (23.12.2015). 755 Journal of Education, Health and Sport eISSN 2391-8306 7 © The Author (s) 2016; This article is published with open access at Licensee Open Journal Systems of Kazimierz Wielki University in Bydgoszcz, Poland Open Access. This article is distributed under the terms of the Creative Commons Attribution Noncommercial License which permits any noncommercial use, distribution, and reproduction in any medium, provided the original author(s) and source are credited. This is an open access article licensed under the terms of the Creative Commons Attribution Non Commercial License (http://creativecommons.org/licenses/by-nc/4.0/) which permits unrestricted, non commercial use, distribution and reproduction in any medium, provided the work is properly cited. This is an open access article licensed under the terms of the Creative Commons Attribution Non Commercial License (http://creativecommons.org/licenses/by-nc/4.0/) which permits unrestricted, non commercial use, distribution and reproduction in any medium, provided the work is properly cited. The authors declare that there is no conflict of interests regarding the publication of this paper. Received: 05.01.2016. Revised 12.02.2016. Accepted: 21.02.2016.     UDK 612.8+616-009+376   CONTROL PSYCHOPHYSICAL CHILDREN'S DEVELOPMENT UNDER THE CORRECTION MOVEMENT DISORDER   Bukhovets B. O.   South Ukrainian National Pedagogical University n.a. K. D. Ushinsky, Odessa, Ukraine   Abstract   This article deals with the problem of determining the effectiveness of the method Bobath, as the main methods of psychophysical condition correction of children with movement disorders. Given the drawbacks of the proposed test detailed rating scale of psychomotor development of children "Map test of motor abilities of children" was adapted and implemented together with the Munich diagnostic testing cards of mental skills and motor abilities of children. The basis of the experiment became the evaluation of basic motor skills in certain positions and determine the true psychophysical age at the beginning and at the end of the course on corrective exercises by Bobath method. Considering the universality, accessibility of data and informative test quality it became possible to assess the stages of psychomotor development and mental qualities forming with the true definition of real psychophysical children age with movement disorders 3-4 years.   Key words: Bobath method, Munich diagnosis, psychomotor development, preschool children, motor disorders.